Kalman filtering approach in the calibration of radar rainfall data - Costa, Marco (2012)
This work presents a comparative study of some models to estimate radar rainfall in real time using the Kalman filtering approach. This comparison adresses the parameters estimation, the assessment of the accuracy estimates obtained by each model and the impact of the number of rain gauges used in the improvement of radar calibration estimates.